2020
DOI: 10.3390/universe6040056
|View full text |Cite
|
Sign up to set email alerts
|

Generalised Uncertainty Relations for Angular Momentum and Spin in Quantum Geometry

Abstract: We derive generalised uncertainty relations (GURs) for orbital angular momentum and spin in the recently proposed smeared-space model of quantum geometry. The model implements a minimum length and a minimum linear momentum, and recovers both the generalised uncertainty principle (GUP) and extended uncertainty principle (EUP), previously proposed in the quantum gravity literature, within a single formalism. In this paper, we investigate the consequences of these results for particles with extrinsic and intrinsi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(129 citation statements)
references
References 49 publications
(174 reference statements)
1
120
0
Order By: Relevance
“…We have shown that relaxing this stringent requirement by introducing a new quantum of action for geometry, β = ħ h, leads to interesting possibilities, with the potential to open up brand new avenues in quantum gravity research [19,32]. These include the proposal that the observed vacuum energy, and the present-day accelerated expansion of the universe that it drives, are related to the quantum properties of space-time [17,18]. In this model, a measurement of the dark energy density constitutes a de facto measurement of the geometry quantisation scale, β, fixing its value to β ħ h × 10 −61 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that relaxing this stringent requirement by introducing a new quantum of action for geometry, β = ħ h, leads to interesting possibilities, with the potential to open up brand new avenues in quantum gravity research [19,32]. These include the proposal that the observed vacuum energy, and the present-day accelerated expansion of the universe that it drives, are related to the quantum properties of space-time [17,18]. In this model, a measurement of the dark energy density constitutes a de facto measurement of the geometry quantisation scale, β, fixing its value to β ħ h × 10 −61 .…”
Section: Discussionmentioning
confidence: 99%
“…In this model, a measurement of the dark energy density constitutes a de facto measurement of the geometry quantisation scale, β, fixing its value to β ħ h × 10 −61 . This essay was written as a non-technical introduction to the smeared-space model, whose formalism was developed over a series of published works [16][17][18][19]32]. It is based on the material presented at the 4th International Conference on Holography, Hanoi, Vietnam (August 2020), and designed to be accessible to a wide and diverse audience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a later analysis by Lake et al, e.g. [28], the EUP term is obtained from a superposition of Euclidean geometries, which are also intrinsically flat like S 1 , but of course with different topology than S 1 , and the EUP term turns out to be positive. Note that, on the other hand, [21] gives good arguments that if the underlying spatial geometry is positively curved, then the corresponding EUP should have a negative correction term and conversely, a negatively curved spatial geometry should give rise to a positive correction term, at least when the geometry is of constant sectional curvature (This is in contrast with the discussion in the previous paragraph, in which the sign of the EUP term appears to be related to the topology of the background, rather than its geometry).…”
Section: The Sign Of Extended Uncertainty Principle Parametermentioning
confidence: 96%
“…Modifying the commutator as in ( 11) comes with some challenges as reviewed in [20][21][22][23]. These challenges are: (i) violation of the equivalence principle; (ii) the "soccer" ball problem [24] (i.e.…”
Section: Minimal Length Via Modified Operatorsmentioning
confidence: 99%